Profitability and Company Growth in Influencing Dividend Policy Moderate by Liquidity - Widati, Sindik; Hidayat, Taufik; Ummah, Rahmatul; Permatasari, Maulina Dyah (Jurnal Akuntansi Bisnis Pelita Bangsa, 2024)
This study aims to analyse the effect of profitability and company growth on dividend policy, with liquidity serving as a moderating variable. The research population consists of manufacturing companies listed on the Indonesia Stock Exchange during 2019-2022. The sample was selected using the purposive sampling method, resulting in 37 companies and a total of 148 observations. Data was collected through the documentary method from the companies' annual reports. Data analysis was conducted using multiple regression and Moderate Regression Analysis (MRA) with the assistance of E-Views software. The results indicated that profitability has a significant negative effect on dividend policy, while company growth does not have an impact on dividend policy. Liquidity has been shown to moderate the effect of profitability on dividend policy but is unable to moderate the effect of company growth on dividend policy. This study provides important implications for investors in understanding the factors that influence the dividend policy of manufacturing companies.